PADHA SYSTEM: THE VILLAGE ADMINISTRATION OF ORAON TRIBE - Dr.Anjela Swarndipika Kujur (Galaxy International Interdisciplinary Research Journal, 2021)
Tribal people are found in every parts of the world in smaller groups or bigger groups. They are nature lovers they worship nature, live in nature and nature is there identity. They lead their life in a systematic way, so in every tribal village the traditional administrative system is followed. In every tribal villages there is a headman who regulates the administrative system.So many different tribes are residing in this world and every tribals have their own way of administration. Talking about Oraon tribe of India and their way of administration, called as Padha system, is one of the redo of an administrative system.